SIMPLE DESIGN OF DYE WATER FILTERING SYSTEM FOR CLEAN AND HEALTHY WATER QUALITY - Timpua, Tony; J,; Pianaung, Robinson; Pongoh, Deitje; Pongoh, Emma; S, (MATTER: International Journal of Science and Technology, 2017)
Demand of clean and healthy water services in the community requires innovation of appropriate technology, for instance through the development of filtering to groundwater systems or to water wells with high turbidity levels in order to meet the water quality standards based on health requirements. The proposed design of dye water filtering system utilizes simple filter media such as sand, gravel, active charcoal and palm fibers. The purpose of this study is to determine the ability of the dye water filtering system to reduce turbidity, contaminations of Ferrum (Fe) and Manganese (Mn) and total coliform bacteria. It is expected that the proposed design of dye water filtering system may produce clean and healthy water with good quality. The laboratory test results indicate that proposed design is effectively to reduce the turbidity level and the Fe concentration that contaminated in the water. Meanwhile, it still is necessary to increase the capability of filtering system by replacing the sand with smaller diameter in order to decrease the levels of Mn and adding disinfectant in order to minimize the concentrate of total coliform bacteria.